FAKTOR-FAKTOR YANG MEMENGARUHI MINAT BACA SISWA SD NEGERI 125 PEKANBARU - Tia Ulfa Amelia; Otang Kurniaman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the low reading interest seen by the few students who visited the library during their free time, whereas high reading interest plays an important role in gaining reading skills. This study aims to describe the factors that influence students 'reading interest and to describe the factors that most influence students' reading interest. This type of research is quantitative descriptive. This research was conducted in SDN 125 Pekanbaru. The population in this study were all high-class students namely class IV, V and VI, which amounted to 148 students. The sample used in this study is a saturated sample, namely sampling techniques if all members of the population are sampled. So the sample in this study was all members of the population, amounting to 148 students, Based on the results of the study, it was found that the factors that affect students' interest in reading consisted of family environment factors, curriculum and school education factors that were not conducive, community infrastructure factors that did not support the increase in public reading interest and the existence and affordability of reading material. The results of the study of four factors that influence interest in reading can be concluded that the factors that most influence students' reading interest SDN 125 Pekanbaru namely the curriculum and school education factors that are not conducive which is equal to 35.474%.